Healthcare Disparities in Atopic Dermatitis in Latin America: A Narrative Review (2023)
ABSTRACT: Introduction: Atopic dermatitis (AD) is a chronic, pruritic skin disease caused by a mixture of genetic, immunological, and environmental factors, characterized by periods of inflammation and remission. In Latin America (LA), the prevalence of AD ranges up to 25% in children and 1-3% in adults. The natural history of the disease for most patients is that AD goes into remission in adolescence and adult life. Only 10-30% of patients continue to have symptoms of the disease in adulthood. There are patients (3-4%) who have the onset of AD during adolescence or after adulthood. Those with limited access to healthcare services, such as diagnosis and treatment, have increased difficulties coping with AD. Healthcare disparities are a complex topic that include social, political, racial/ethnic, and geographical factors. Publications about healthcare disparities in AD in LA are scarce. As a result, recognizing and resolving healthcare inequalities is critical to improving the treatment and quality of life (QoL) of individuals with AD. Methods: A panel of Latin American experts in dermatology and allergies was provided with a series of relevant questions to address before a multiday conference. During this conference, the entire group discussed and edited each narrative through numerous drafts and rounds of discussion until they reached a consensus. Results: This paper examines the barriers to equal access to care and recommends realistic actions to overcome them. Inadequate disease knowledge, cultural and linguistic barriers, stigmatization, maldistribution of resources, absence of local clinical practice guidelines, arduous patient journey, and limited consultation time were identified as causes of health inequality. Conclusions: Among the suggested solutions are enhanced education for healthcare professionals, patients, and the general public, a focus on underprivileged communities, telemedicine and telementoring, translators, multidisciplinary teams, and local living clinical practice guidelines. Keywords: Atopic dermatitis; Eczema in Latin America; Healthcare disparities in Latin America; Latin America; Latin America skin disease treatment options; Quality of life for people with atopic dermatitis.